CHALLENGES IN WRITING ACADEMIC RESEARCH: AN EXPLORATION OF MASTER’S STUDENTS’ EXPERIENCES - Siti Kholija Sitompul; Amira Wahyu Anditasari (English Education Department, 2022)
This study attempted to investigate the students’ difficulties in research writing involving 39 master’s students majoring in English Language Education at one of the universities in Malang. The data on the thesis writing difficulties were gathered through a close-ended questionnaire designed based on the theory proposed by Harris (2020), consisting of three aspects: research skills in the introduction, research method, and finding and discussion parts. The data was analyzed quantitatively by measuring the mean, mode, and percentage from each scale. The results revealed that many master’s students encountered difficulties in most three aspects. First, one-third of 39 students perceived difficulty in the introduction part, such as selecting a research topic and formulating research problems. Second, the students also affirmed that they found challenging in the research method part, such as the dilemma of selecting an appropriate method, determining the sample, and designing instruments in which the results were slightly different from the students who were in the level of disagreement. However, finding appropriate instruments, determining the questionnaire scale, and collecting data were less problematic. Third, the study highlighted that the students found it difficult to process data, sort the data the results, and conclude the results by elaborating on research implications. This study concluded that master’s students still faced difficulties although they have learned research at undergraduate and master’s levels. It was recommended that further studies should intensively investigate students’ difficulties and factors in research in linguistics.